KAJIAN TEORI STAKEHOLDERS TERKAIT PERLINDUNGAN HUKUM BAGI PEMEGANG SAHAM MINORITAS - Munawarah, Iva Yulia (The Juris, 2017)
Based on the theory, stakeholders are investors and creditors only, but among others the government, customers, suppliers, employees / labor, society and the environment. The government can be regarded as stakeholders for the company because the government has an interest in the activities of a company and the existence of the company as one element of social systems in a country. Therefore the company can not ignore the role of government in running business management.